Medicine balls training in the sequence of complex handball training versus only handball training: effects on physical fitness in pre-adolescence female handball players - Natalia Chukhlantseva (Baltic Journal of Health and Physical Activity, 2023)
Introduction: The inclusion of the training process of pre-adolescent female athletes with additional means helps to optimize exercise influences. The study aims to estimate the influence of a 16-week program of handball training with medicine balls in comparison with a program of handball training on the physical and special training of beginner handball players. Methods: Female athletes were randomly divided into an experimental (n = 30; 11.23 ±0.41 years) and a control (n = 32; 10.99 ± 0.4 years) group. Training sessions of both groups were conducted according to the existing curriculum, but the experimental group replaced part of the usual regimen by training with medicine balls once a week. Results: Both groups improved, but more markedly in the experimental group than in the control group in the increase of leg explosive power (Δ% = 7.73, p < 0.05, d = 0.67), trunk muscle strength (Δ% = 16.9, p < 0.05, d = 0.88) and ball handling level indicators: dribbling the ball (δ% = 13.41, p < 0.05, d = 1.07), throwing the handball ball with one hand (Δ% = 28.6, p < 0.05, d = 1.6). Conclusions: A program of workouts with medicine balls enables the improvement of important components of physical performance. Inclusion of the training process of pre-adolescent female athletes with additional means helps to optimize exercise influences.